Proceedings of the Companion Publication of the 19th International Conference on Intelligent User Interfaces 2014
DOI: 10.1145/2559184.2559186
|View full text |Cite
|
Sign up to set email alerts
|

Toward emotion regulation via physical interaction

Abstract: Emotions can be regulated to fit a task in order to enhance task performance. Motor expressions can help regulate emotion. This paper briefly reports ongoing work on the design of physical interactions based on motor expressions that can help regulate emotion to fit a task. We argue that to be effective, such interactions must be made meaningful in relation to ongoing appraisal processes, and that such interactions can help regulate emotion via congruence, suppression, or incompatibility. We present previous w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…This study explored the scenario where a textile-based emotion wear t-shirt would be available to users. Initially, we reviewed the literature to identify the body movements that impact human emotions [ 7 , 8 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. We identified the flexion and extension movements that affect the angle between two parts of the body.…”
Section: E-motionwearmentioning
confidence: 99%
See 3 more Smart Citations
“…This study explored the scenario where a textile-based emotion wear t-shirt would be available to users. Initially, we reviewed the literature to identify the body movements that impact human emotions [ 7 , 8 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. We identified the flexion and extension movements that affect the angle between two parts of the body.…”
Section: E-motionwearmentioning
confidence: 99%
“…While open and closed arms and neck flexion movements belong to the torso expanding motions, the elbow and shoulder flexion/extension belong to the upward-opening body movements. These movements are thought to contribute to enhancing positive emotions [ 7 , 8 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Moreover, the smart t-shirt covers the upper body allowing the users to conveniently perform these movements in any posture (such as standing or sitting).…”
Section: E-motionwearmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, it has been suggested that there is a bi-directional relationship between emotion and body motor behaviour [5,6]. Body movements can be used not only to express emotions but also to influence how we feel due to the mirror neurons.…”
Section: Reflectionmentioning
confidence: 99%